Cardiograms and Electrography Are Crucial Diagnostic Procedures In Pregnant Women - Kizi, Rozmetova Roziyakhon Yakubboy (Health & Medical Sciences, 2024)
Certain examinations place significant emphasis on the gestation period. Strictly passing every examination is of utmost importance for every woman, as failure to do so may result in the birth of children with various deformed and incapacitating disorders. The diagnostic procedures of cardiotomy, electrocardiography, ultrasonography, doppler ultrasonography, and phenocardiography are highly significant for pregnant women. Every expectant mother should undertake these tests comprehensively. The duration of pregnancy and developmental abnormalities like as hypotrophy, hydrocephaly, and microcephaly can be determined using these techniques. Furthermore, these techniques facilitate the surveillance of the foetal placenta and the estimation of the water content, particularly in cases of multiple pregnancies. Sonography examination is safe for both the pregnant woman and the developing foetus. Today, X-ray diagnostics is seldom employed. However, this approach strictly relies on the use of the vagina as the sole means of assessing the state and abnormalities of the foetus, in the absence of ultrasound equipment.